Schistosomiasis in the Democratic Republic of Congo: a literature review. Issue 1 (December 2015) - Madinga, Joule; Linsuke, Sylvie; Mpabanzi, Liliane; Meurs, Lynn; Kanobana, Kirezi; Speybroeck, Niko; Lutumba, Pascal; Polman, Katja
Abstract Schistosomiasis is a poverty-related parasitic infection, leading to chronic ill-health. For more than a century, schistosomiasis has been known to be endemic in certain provinces of the Democratic Republic of Congo (DRC). However, a clear overview on the status of the disease within the country is currently lacking, which is seriously hampering control. Here, we review the available information on schistosomiasis in DRC of the past 60 years. Findings and data gaps are discussed in the perspective of upcoming control activities. An electronic literature search via PubMed complemented by manual search of non-peer-reviewed articles was conducted up to January 2015. The search concerned all relevant records related to schistosomiasis in the DRC from January 1955 onwards. A total of 155 records were found, of which 30 met the inclusion criteria. Results were summarized by geographical region, mapped, and compared with those reported sixty years ago. The available data reported schistosomiasis in some areas located in 10 of the 11 provinces of DRC. Three species ofSchistosoma were found:S. mansoni, S. haematobium andS. intercalatum . The prevalence of schistosomiasis varied greatly between regions and between villages, with high values of up to 95 % observed in some communities. The overall trend over 60 years points to the spread of schistosomiasis to formerly non-endemic areas. The prevalence of schistosomiasis has increased in rural endemic areas and decreased in urban/peri-urban endemic areas of Kinshasa. Hepatosplenomegaly, urinary tract lesions and anaemia were commonly reported in schistosomiasis endemic areas but not always associated with infection status. The present review confirms that schistosomiasis is still endemic in DRC. However, available data are scattered across time and space and studies lack methodological uniformity, hampering a reliable estimation of the current status of schistosomiasis in DRC. There is a clear need for updated prevalence data and well-designed studies on the epidemiology and transmission of schistosomiasis in DRC. This will aid the national control program to adequately design and implement strategies for sustainable and comprehensive control of schistosomiasis throughout the country.